Chemical constituents and bioactivity of Mitrella Kentii (Bl.) miq. (Annonaceae) / Ainnul Hamidah Syahadah binti Azizan - Azizan, Ainnul Hamidah Syahadah (2013)
The phytochemical and bioactivity studies on Mitrella kentii species from Annonaceae family have been performed. The extraction of phytochemicals from dried and ground plants were performed using conventional method extractions; Soxhlet extractor and Cold-extraction. The isolation of pure compounds from crude extracts were carried out by using various chromatographic methods such as column chromatography (CC), thin layer chromatography (TLC) and preparative thin layer chromatography (PTLC). The structural elucidations of the isolated compounds were established based on the spectroscopic techniques such as UV-Vis, IR, MS, 1D-NMR (1H-NMR and 13C-NMR), 2D-NMR (COSY, DEPT, HSQC and HMBC) and single crystal X-ray diffraction analysis. From this study, nine known compounds have been isolated and characterised from the stem bark of Mitrella kentii. These compounds are chalcones, desmosdumotin C MK1 and its tautomer, 2'-cinnamoyl-3'-hydroxy-5'-methoxy-4',6',6'-trimethylcyclohexa-1',1-dienone MK2, terpenoids, stigmasta-4-en-3-one MK3 and stigmasta-4,22-diene-3,25-dione MK4, flavanone, 6-hydroxy-5,7-dimethoxy-2-phenylchroman-4-one MK5, benzyl benzoate MK6, oxybis(ethane-2,1-diyl) dibenzoate MK7, oxoaporphine alkaloids, liriodenine MK8 and atherospermidine MK9. All these compounds were isolated for the first time from Mitrella kentii species except for MK8. The isolated compounds were elucidated using spectroscopic techniques and by comparison of their spectral data with those previously reported in the literatures. For the bioactivities study, only the major compound; MK1 in this species was investigated further in the bioactivities. Firstly, the toxicity study on MK1 showed that there are no abnormal physiological or behavioural changes, body weight alteration at any time of observation at the doses used during the 14 days. The anti-ulcer experiment was performed for the MK1 and result showed that the rat pretreated with MK1, or omeprazole (standard) considerably reduced ulcer area formation compared to ulcer control group. MK1 at doses of 5, 10, 20 mg/kg b.w, was observed to inhibit ulcer formation by 69.77%, 90.18% and 86.56%, respectively. MK1 at doses 10 and 20 mg/kg protect stomach from ulceration significantly (p<0.05) higher than that obtained by omeprazole at dose 20 mg/kg with 79.07%. Therefore, MK1 demonstrated better result than omeprazole. In vitro anti-Helicobacter pylori activity experiment also showed that MK1 represents minimum inhibitory concentration MIC of >250 μg/ml and minimum bactericidal concentration MBC >250 against H. pylori NCTC11637 strain and moderately MIC of 125 μg/ml and MBC of 250 μg/ml against H. pylori J99. Hence, MK1 displayed good result for anti- H. pylori effect. For the FRAP experiment, MK1 exhibited FRAP value of 120.7 ± 0.001 significantly (p < 0.05) which was lower than the positive controls used in this study; quercetin, 2046.7± 0.024, gallic acid, 2562.7± 0.024 and ascorbic acid, 879.3 ± 0.005, respectively. Meanwhile the DPPH assay did not show any significant inhibition in the dose dependant manner used in the study. Therefore, it can be concluded that MK1 exerts its antiulcer effect through indirect antioxidant mechanism. In addition, MK1 also maintained non protein sulfhydryl (NP-SH) content, glutathione (GSH) level, decreased malondialdehyde (MDA) level but didn’t affect nitric oxide (NO) level or cycloxygenase-2 (COX-2) activity. MK1 also showed an increase 70 kilodalton heat shock proteins (HSP-70) activity and decrease of control Bax proteins expression in ulcerated tissue.